2018
DOI: 10.1186/s12871-018-0508-6
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine infusion as an analgesic adjuvant during laparoscopic сholecystectomy: a randomized controlled study

Abstract: BackgroundDexmedetomidine (DEX) has sedative, sympatholytic and analgesic effects and might be beneficial if used as an adjuvant to: improve analgesia; modulate haemodynamic responses to intubation and pneumoperitoneum and; reduce the number of opioid-associated adverse events. The aim of this study was to evaluate the efficacy and safety of DEX infusion during elective laparoscopic cholecystectomy (LC).MethodsA randomized, single-centre, parallel-group, placebo-controlled study was carried out between May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
45
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 16 publications
1
45
1
5
Order By: Relevance
“…Based on data from 15 RCTs , with a total of 2426 ICU patients, we found no evidence of a decrease in mortality in the dexmedetomidine group compared with placebo OR (95%CI) 0.86 (0.66–1.10), p = 0.23, I 2 = 0%; moderate quality of evidence and inconclusive trial sequential analysis), see Supporting Information (Fig. S1).…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Based on data from 15 RCTs , with a total of 2426 ICU patients, we found no evidence of a decrease in mortality in the dexmedetomidine group compared with placebo OR (95%CI) 0.86 (0.66–1.10), p = 0.23, I 2 = 0%; moderate quality of evidence and inconclusive trial sequential analysis), see Supporting Information (Fig. S1).…”
Section: Resultsmentioning
confidence: 96%
“…Eight trials with 1090 patients indicated a shorter time to extubation in patients who received dexmedetomidine, MD (95%CI) −1.74 h (−2.64 to −0.84), p < 0.001, I 2 = 100%). The test of heterogeneity was high in the pooled effect; see Supporting Information (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations